Mercy and Justice: the Place of Equity - Ruiz Miguel, Alfonso (2017)
The essay deals with the relationship between mercy and equity as a form of indulgent justice. Starting from the Aristotelian concept of equity, the essay studies the relationship between indulgency and normative overinclusion and underinclusion, considers the reach of equity in criminal law and concludes analysing the relation between judicial equity and legislation.